Anti-tumor immune modulation and favorable survival outcomes in uterine corpus endometrial carcinoma: insights from PIK3CA/ARID1A co-mutation analysis - Dongmei Han; Caihong Wu; Hao Jin (Discover Oncology)
Abstract Background Uterine corpus endometrial carcinoma (UCEC) is the most prevalent cancer of the female reproductive system, posing significant risks to women's reproductive health and imposing considerable economic burdens on families and society due to high treatment costs. Methods The study population comprised 529 UCEC patients who were selected and retrieved from the cBioPortal public database for a comprehensive integrated analysis. This study aims to explore the prognostic significance of co-mutation in PIK3CA/ARID1A genes in UCEC, utilizing various bioinformatics approaches, including differential expression genes (DEGs) analysis, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, Gene Set Enrichment Analysis (GSEA), immune infiltration analysis, and the establishment of nomogram model. Results PIK3CA/ARID1A co-mutation group had a better prognosis than the other three groups. The co-mutation of PIK3CA/ARID1A was associated with a significantly improved overall survival (OS) in patients with UCEC and immunotherapy markers. This result was further corroborated in the MSK cohort, reinforcing the robustness of our observations. Our findings revealed that 222 genes were upregulated and 1,464 genes downregulated in the co-mutation group compared to the non-co-mutation (NCM) group, providing a molecular basis for understanding the biological roles of these gene mutations in UCEC. Additionally, pathway analysis identified significant enrichment in immune-related pathways, emphasizing the potential for co-mutation to influence tumor progression via immune modulation. Notably, patients with co-mutations exhibited improved overall survival (P < 0.05), suggesting their role as vital prognostic markers. The developed Cox proportional hazards model demonstrated high predictive accuracy (C-index = 0.835), supporting personalized management for UCEC patients. Conclusion In conclusion, this study underscores the importance of PIK3CA and ARID1A co-mutations in UCEC, advocating for their further exploration in clinical applications and therapeutic strategies.